Dietary strategies for remission of type 2 diabetes: A narrative review. Issue 1 (1st September 2021) - Brown, Adrian; McArdle, Paul; Taplin, Julie; Unwin, David; Unwin, Jennifer; Deakin, Trudi; Wheatley, Sean; Murdoch, Campbell; Malhotra, Aseem; Mellor, Duane
Abstract: Type 2 diabetes (T2DM) is a growing health issue globally, which, until recently, was considered to be both chronic and progressive. Although having lifestyle and dietary changes as core components, treatments have focused on optimising glycaemic control using pharmaceutical agents. With data from bariatric surgery and, more recently, total diet replacement (TDR) studies that have set out to achieve remission, remission of T2DM has emerged as a treatment goal. A group of specialist dietitians and medical practitioners was convened, supported by the British Dietetic Association and Diabetes UK, to discuss dietary approaches to T2DM and consequently undertook a review of the available clinical trial and practice audit data regarding dietary approaches to remission of T2DM. Current available evidence suggests that a range of dietary approaches, including low energy diets (mostly using TDR) and low carbohydrate diets, can be used to support the achievement of euglycaemia and potentially remission. The most significant predictor of remission is weight loss and, although euglycaemia may occur on a low carbohydrate diet without weight loss, which does not meet some definitions of remission, it may rather constitute a 'state of mitigation' of T2DM. This technical point may not be considered as important for people living with T2DM, aside from that it may only last as long as the carbohydrate restriction is maintained. The possibility of actively treating T2DM along with the possibility of achieving remission should be discussed by healthcare professionals with people living with T2DM, along with a range of different dietary approaches that can help to achieve this. Abstract : Different dietary approaches, as well as bariatric surgery, have been shown to facilitiate remission of type 2 diabetes Practice points: Type 2 diabetes (T2DM) remission should be considered as a treatment goal for people living with T2DM (especially for those within 6 years from being diagnosed). The ability to achieve this may be influenced by duration of diabetes, weight loss and gender. Therefore, it should be positively discussed with this in mind. Based on the evidence from clinical trials weight loss (typically 15 kg or greater) is the main driver and predictor of remission. However, more data are needed so that it is more reflective of an ethnically diverse population. Based on evidence from clinical trials, maintenance of weight loss appears to be the main driver of continued remission, and this therefore needs to be a key focus of the planning and delivery of all services designed to achieve remission. If a diet low in carbohydrate is sustainable to the individual, normoglycaemia may be maintained in the absence of weight loss, although evidence is limited and loss of remission is likely to occur if carbohydrate restriction ceases. Total dietary replacements (TDR) and low carbohydrate diets have been demonstrated as being effective in facilitating weight loss and remission of T2DM. Evidence of effectiveness beyond 2 years is limited. The dietary approach should be one which the individual can maintain for the long term. TDR and low carbohydrate diets, if appropriately supported, are considered safe and should not be avoided in suitable individuals who find these approaches acceptable. Clinicians should therefore aim to support their use within clinical practice as part of person‐centred diabetes care. Programmes supporting people toward achieving remission need to be structured and offer continued, regular support, including the involvement of dietitians (mandated by the National Health Service England).